The pity party 8th grade in the life of me, Cass - Pollet, Alison (New York Orchard Books, 2005)
When Cass Levin, an orphaned eighth-grader at Elston Prep in New York City, begins a frienship with Rod Punkin, her world begins to change
Hurg
5 8
Keywords: Preparatory schools -- Fiction; Schools -- Fiction